O pedagogo na Educação Profissional e Tecnológica: plano de atividade pedagógica - Valle, Maria Raimunda Lima (2019)
The pedagogue's activity in Professional and Technological Education constitutes the object of study of this investigative process. The work is inserted in the research line Management and Organization of Pedagogical Spaces in Professional and Technological Education, whose goal is to understand the pedagogue’s activity in the Professional and Technological Education, in the context of the Federal Institute of Amazonas, specifically, in the Manaus Center Campus. The specific objectives were to identify the activities developed by pedagogues in the academic departments of IFAM-CMC, analyze pedagogical activities in front of the challenges of EPT, and systematize a pedagogical activity plan from the perspective of History-Cultural Theory and Activity Theory, aiming at contextualized and integrative actions. The investigative process focused on the Qualitative Research and the Historical Materialistic Dialectics approach, defining the Research-Action as the methodological proposal in order to investigate it’s praxis of the and with the pedagogues in the context of EPT. The instruments and techniques used were the observation, the online questionnaire and the collective interviews through the conversation circles with the participation of ten active servants, where seven were pedagogues, two were technicians in educational matters and one was a teacher, all working in the departments and academic sectors of the IFAM-CMC and performing the position or pedagogical function. The treatment and interpretation of the data were performed based on Bardin's analysis of CA (Content Analysis). The results of the research presented the limitations of pedagogical work in relation to the conditions of administrative structures and their organizational forms and the possibilities of overcoming through integrative pedagogical actions, in addition of the need to promote formative processes of these professionals aiming contributions to EPT. The educational result of the research culminated in the collective systematization of a pedagogical activity planned to be developed in a participatory and collaborative way by pedagogues and the school community and proposes relevant contributions to integral human formation and improvement of teaching practices in the Ifs.